Correlation of the rates of solvolysis of tert-butyl chlorothioformate and observations concerning the reaction mechanism - Kyong, Jin Burm; Lee, Yelin; D'Souza, Malcolm John; Mahon, Brian Patrick; Kevill, Dennis Neil (European Journal of Chemistry, 2012)
The “parent” tertiary alkyl chloroformate, tert-butyl chloroformate, is unstable, but the tert-butyl chlorothioformate (1) is of increased stability and a kinetic investigation of the solvolyses is presented. Analyses in terms of simple and extended Grunwald-Winstein equations are carried out. The original one-term equation satisfactorily correlates the data with sensitivity towards changes in solvent ionizing power of 0.73±0.03. When the two-term equation is applied, the sensitivity towards changes in solvent nucleophilicity of 0.13±0.09 is associated with a high (0.17) probability that the term that it governs is not statistically significant.